Biodegradable mulch as microclimate modification effort for improving the growth of horenso; Spinacia oleracea L. - A. Iriany; F. Hasanah; D. Roeswitawati; M.F. Bela (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Increasing global temperature imposes large risks to food security globally and regionally. Besides, adaptation effort on cultivation practices, such as mulching, is urgent to overcome environmental problem due to certain material used, commonly plastic that is not biodegradable. Biodegradable mulch is a mulch that could be degraded by microorganism and made from renewable organic materials. It plays a role in carbon sequestration and will contribute carbon and nutrients to the soil after being degraded. This current research aimed at investigating soil microclimate under various biodegradable mulch compositions and optimizing the compositions of biodegradable mulch that can be used to support the growth of short-cycle crops i.e. horenso (Spinacia olearecea L.). METHODS: This study was carried out using a simple randomized complete block design with one control (without mulch) and five treatments (biodegradable mulch compositions), namely the percentage of water hyacinth (40-80%) and coconut coir (20-60%).  FINDINGS: All tested biodegradable mulch compositions could modify microclimate by decreasing 1-2°C of soil temperature and maintaining the soil moisture within the range of 63-84%. Although there was no significant difference in the growth and yield of horenso among the differing biodegradable mulch compositions, the biodegradable mulch composition treatments resulted in signficantly higher value than the control (without mulch). The biodegradable mulch composition treatments could increase fresh shoot weight around 38-55%, fresh root weight for about 55-94%, and dry shoot weight approximately by 1.6-2.8 times compared to the control (without mulch).  CONCLUSION: This finding has emphasized that all tested biodegradable mulch compositions are potentially used as mulch for horenso (Spinacia oleracea L.) cultivation. This study provide information in the formulation of biodegradable mulch to adapt the compositions on other short-cycle crops and other horticulture crops.